1996
DOI: 10.1007/bf01411064
|View full text |Cite
|
Sign up to set email alerts
|

Migration of human glioma cells in response to tumour cyst fluids

Abstract: Glial tumours often show high degrees of local invasion that lead to local recurrence of the disease. Extracellular matrix components as well as soluble factors may play a critical role in this poorly understood process. Cyst fluid from human brain tumours may accumulate such autocrine produced factors and may represent a source were those factors may be easily obtained and studied. We have studied the effect of cyst fluids harvested from 17 glial tumours, 3 meningiomas, and three metastases on the motility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Several experimental systems have demonstrated that there may be an inverse correlation between cell motility and the proliferation of a cell population. Glioma cells, when stimulated to migrate by permissive matrix substrates or soluble motility factors, show a temporarily lowered proliferation rate (Giese et al 1996a;Giese et al 1996b). Control of motility is tightly controlled by matrix adhesion (Giese et al 1994;Giese et al 1995;Giese et al 1996b;Palacek et al 1997).…”
Section: Perspectives: How To Hit a Moving Targetmentioning
confidence: 99%
“…Several experimental systems have demonstrated that there may be an inverse correlation between cell motility and the proliferation of a cell population. Glioma cells, when stimulated to migrate by permissive matrix substrates or soluble motility factors, show a temporarily lowered proliferation rate (Giese et al 1996a;Giese et al 1996b). Control of motility is tightly controlled by matrix adhesion (Giese et al 1994;Giese et al 1995;Giese et al 1996b;Palacek et al 1997).…”
Section: Perspectives: How To Hit a Moving Targetmentioning
confidence: 99%